2021
DOI: 10.1371/journal.pone.0250078
|View full text |Cite|
|
Sign up to set email alerts
|

Widespread mortality of trembling aspen (Populus tremuloides) throughout interior Alaskan boreal forests resulting from a novel canker disease

Abstract: Over the past several decades, growth declines and mortality of trembling aspen throughout western Canada and the United States have been linked to drought, often interacting with outbreaks of insects and fungal pathogens, resulting in a “sudden aspen decline” throughout much of aspen’s range. In 2015, we noticed an aggressive fungal canker causing widespread mortality of aspen throughout interior Alaska and initiated a study to quantify potential drivers for the incidence, virulence, and distribution of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…SAD was reported to not affect saplings (Worrall et al 2008). The aspen running canker in Alaska is most destructive on saplings in the understory of intermediate-aged and mature stands, but is nearly absent from younger aspen growing in early-successional stands (Ruess et al 2021). Aspen running canker has been observed primarily on live Fig.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…SAD was reported to not affect saplings (Worrall et al 2008). The aspen running canker in Alaska is most destructive on saplings in the understory of intermediate-aged and mature stands, but is nearly absent from younger aspen growing in early-successional stands (Ruess et al 2021). Aspen running canker has been observed primarily on live Fig.…”
Section: Discussionmentioning
confidence: 97%
“…standing trees with turgid bark and recently dead trees with conspicuous sunken cankers showing retention of fine terminal twigs in canopies. These symptoms represent very recent mortality (1-2 years) and rarely display the branch dieback and reduced-canopy typical of decline symptoms (personal observations, Ruess et al 2021). In SAD, mature trees show extensive branch dieback while active cankers are generally not observed (Marchetti et al 2011); insects and diseases were reported to be minor secondary contributors to droughtassociated mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations